2013
DOI: 10.1371/journal.pone.0069483
|View full text |Cite
|
Sign up to set email alerts
|

The Synthetic Amphipathic Peptidomimetic LTX109 Is a Potent Fungicide That Disturbs Plasma Membrane Integrity in a Sphingolipid Dependent Manner

Abstract: The peptidomimetic LTX109 (arginine-tertbutyl tryptophan-arginine-phenylethan) was previously shown to have antibacterial properties. Here, we investigated the activity of this novel antimicrobial peptidomimetic on the yeast Saccharomyces cerevisiae. We found that LTX109 was an efficient fungicide that killed all viable cells in an exponentially growing population as well as a large proportion of cells in biofilm formed on an abiotic surface. LTX109 had similar killing kinetics to the membrane-permeabilizing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 74 publications
1
29
0
Order By: Relevance
“…It was shown that LTX109 compared favorably with both terbinafine and amorolfine for the ex vivo treatment of these persistent fungal infections in a very rapid fashion. The fungicidal mode of action of LTX109 on the fungal cells has also been studied and shown to operate via nonspecific destabilization of the fungal plasma membrane . Given these very promising results from the earlier antifungal studies, and a structural resemblance to the highly active antifungal aryl‐alkyl‐lysines recently reported by Haldar and coworkers, it was decided to also screen a selection ( 9 , 12 , 13 , 15 , 16 , and 18 ) of the prepared DKPs against a panel of 5 human pathogenic fungi from the Candida genus (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that LTX109 compared favorably with both terbinafine and amorolfine for the ex vivo treatment of these persistent fungal infections in a very rapid fashion. The fungicidal mode of action of LTX109 on the fungal cells has also been studied and shown to operate via nonspecific destabilization of the fungal plasma membrane . Given these very promising results from the earlier antifungal studies, and a structural resemblance to the highly active antifungal aryl‐alkyl‐lysines recently reported by Haldar and coworkers, it was decided to also screen a selection ( 9 , 12 , 13 , 15 , 16 , and 18 ) of the prepared DKPs against a panel of 5 human pathogenic fungi from the Candida genus (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The fungicidal mode of action of LTX109 on the fungal cells has also been studied and shown to operate via nonspecific destabilization of the fungal plasma membrane. 68 Given these very promising results from the earlier antifungal studies, and a structural resemblance to the highly active antifungal aryl-alkyl-lysines recently reported by…”
Section: Biological Evaluation On Fungal Strainsmentioning
confidence: 87%
“…The phase IIa clinical trial was completed by LytixBiopharma for the topical treatment of impetigo and nasal decolonization of MRSA. Additionally, the preclinical study for the treatment of diabetic foot ulcers via topical administration is ongoing [5,66,88].…”
mentioning
confidence: 99%
“…For example, when sugar and ion transporter, OmpF, was deleted, and the long chain fatty acids transporter, FadL, was overexpressed in E. coli , membrane integrity was enhanced and the fatty acid titer improved (39); (ii) Phospholipids: Membrane integrity can also be altered by modifying the distribution of phospholipid head groups, by adjusting phospholipid saturation, and by altering phospholipid acyl chain length (14, 40). For instance, when pssA, a phosphatidylserine synthase, was overexpressed, PE content increased and membrane integrity was enhanced, as a result of which bio-renewable fuel tolerance and titer was improved (12); (iii) Sterols: Sterol serves as an essential cell membrane component, where deletion of CgMed3AB decreased lanosterol, zymosterol, fecosterol, and ergosterol content, thereby reducing the membrane integrity of Candida glabrata (19); (iv) Sphingolipids: Sphingolipid metabolism plays an important role in membrane integrity (41). When sphingolipid biosynthesis genes were deleted in S. cerevisiae , the resultant strains exhibited resistance to amphipathic peptidomimetic LTX109, which decreased membrane integrity (41).…”
Section: Discussionmentioning
confidence: 99%